Core summary for IODP Site 389-M0109 - Jody M Webster; Ana Christina Ravelo; Hannah Grant; Margaret S Stewart; Marisa Rydzy; Erwan Le Ber; Nicola Allison; Ryuji Asami; Brian Boston; Juan-Carlos Braga; Logan Brenner; Xuefei Chen; et al. (PANGAEA, 2025)
List of cores recovered from the above given site on International Ocean Discovery Program (IODP) Expedition 389 (Hawaiian Drowned Reefs) during the offshore phase of this expedition. The offshore phase took place between 2023-08-31 and 2023-10-31 onboard multipurpose vessel MMA Valour sailing from and to Barbers Point Harbor, Hawai extquotesinglei, USA. Cores have been acquired by Benthic extquotesingles fifth-generation Portable Remotely Operated Drill (PROD5). According to IODP core type nomenclature, cores recovered by push coring mode are labelled by the letter P, those recovered by rotary coring mode are labelled by the letter "R" and the letter "W" indicates intervals drilled without coring in wash down mode. For further methodological information see methods chapter in0.167emWebster, J.M. et al., 2025 https://doi.org/10.14379/iodp.proc.389.2025